Carbon Nanotubes: In Situ Monitoring the Role of Working Metal Catalyst Nanoparticles for Ultrahigh Purity Single‐Walled Carbon Nanotubes (Adv. Funct. Mater. 40/2013). (23rd October 2013) - Chen, Tian‐Chi; Zhao, Meng‐Qiang; Zhang, Qiang; Tian, Gui‐Li; Huang, Jia‐Qi; Wei, Fei
<x xml:space="preserve">Abstract</x> The role of metal catalysts in the creation of ultrapure single‐walled carbon nanotubes (SWNCTs) is explored by Q. Zhang, F. Wei, and co‐workers on page 5066. They promote efficient growth of SWCNTs via partial oxidation of metal@C nanoparticles by CO2, and subsequent acid treatment. This in situ study of the chemical vapor deposition growth and CO2 oxidation of SWCNTs reveals in real‐time that the key lies in the low content of nanocarbon impurities and the catalytic oxidation being performed in the proper operation windows. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>